Essential tremor: predictors of disease progression in a clinical cohort. Issue 11 (25th July 2006) - Putzke, J D; Whaley, N R; Baba, Y; Wszolek, Z K; Uitti, R J
Abstract : Objectives: To examine the utility of baseline factors to predict disease progression among a clinical cohort of patients diagnosed with essential tremor. Measures: Tremor Rating Scale (TRS). Methods: A clinical series of 128 consecutive patients diagnosed with essential tremor was included for study. 45 (35%) patients had at least one follow-up exam (mean = 3.6 years). Baseline predictive factors examined included age, age at onset of symptoms, disease duration, sex, handedness, total tremor rating score, asymmetric tremor ratings, location of initial tremor onset, use of drugs for movement disorders, ETOH responsiveness of tremor, association of head or neck tremor, history of depression, familial history of essential tremor, Parkinson's disease, Alzheimer's disease and other movement disorders. Results: On average, the TRS total score increased by <1 point per year before the first visit to the clinic and by about 2 points per year during the observed study period. The increase of 2 points per year during the observed study period represented an approximate 12% annual change from the mean TRS total score at the first clinic visit. Significant (p<0.05) predictive factors associated with increased tremor severity at the initial clinic visit included older age, longer disease duration, use of movement disorder drugs and the presence of voice tremor (r = 0.24, 0.27, 0.25, 0.19). The major factors associated with an increase in tremor severity from the initial clinic visit to the last follow up included asymmetrical tremor ratings, unilateral initial tremor onset and longer follow-up duration (r = 0.32, 0.31, 0.30). Multivariate regression analysis accounted for about 17–30% of the variance in tremor ratings (p<0.05). Conclusion: Essential tremor is a slow, progressive disease. The rate of disease progression and the factors associated with disease progression may vary throughout the disease course.